Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Bimbingan Belajar LPR - Siti Mabrur Rachmah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The purpose of this study is to analyze the effect of service quality on customer satisfaction at LPR Course. This research adopts a quantitative approach, utilizing primary data collected from customers or students of the LPR Course as the sample. The data were gathered using a saturation sampling technique, involving 20 respondents. The study employs simple regression analysis to examine the relationship between service quality and customer satisfaction. The findings reveal that service quality has a significant and positive effect on customer satisfaction at LPR Course.